Kinetic study of the thermolysis process of oil sludge (atasu-alashankou) with nickel, cobalt and iron deposited on microsilicate - Tyanakh, Sairagul; Baikenov, Murzabek; Tusipkhan, Almas; Aitbekova, Darzhan; Balpanova, Nazerke; Yun, Ma Feng (Eastern-European Journal of Enterprise Technologies, 2022)
The object of research is the process of thermal degradation of oil sludge in the presence of heterogeneous catalysts. The creation of efficient technological processes for processing the organic part of oil sludge into motor fuels, raw materials for petrochemicals and the disposal of microsilicate is an important urgent task, the solution of which will allow to obtain a significant economic and environmental effect. The problem to be solved is to establish the general kinetic laws of the process of thermal degradation of oil sludge in the presence of microsilicate with deposited metals. The advantage of the Ozawa– Flynn–Wall method is that it is possible to determine the kinetic parameters for each value of oil sludge conversion, that is, for different stages of thermal degradation. The activation energy of oil sludge 67.1 kJ/mol, and with a catalyst 59 kJ/mol are calculated for each degree of conversion (α), respectively. The value of the correlation coefficient was (R2≥0.997) provides good convergence with experimental results. Compared with other methods of thermal processing of oil sludge, catalytic thermal degradation has a number of advantages: relatively low process temperatures (400–650 °C), low sensitivity to the composition of raw materials and the processing process, which meets all modern requirements of chemical production. Regularities of thermokinetic parameters of thermal decomposition of oil sludge were studied using raw materials obtained during the process of oil transportation, in the presence of catalyst with applied metal (nickel, iron, cobalt) to microsilicate. Obtained results of oil sludge decomposition kinetics can be used in creating a database for mathematical modeling of process of heavy hydrocarbon raw materials processing